Mechanistic modeling of lipid nanoparticle (LNP) precipitation via population balance equations (PBEs) - Sunkyu Shin; Cedric Devos; Aniket Pradip Udepurkar; Pavan K. Inguva; Allan S. Myerson; Richard D. Braatz (Chemical Engineering Journal, 2025)

Fecal biomarkers in Italian anthropogenic soil horizons and deposits from Middle Ages and bronze age - M. Bortolini; C. Nicosia; E. Argiriadis; G. Pojana; Y. Devos; D. Battistel (Quaternary Science Reviews, 2024)

Above- and belowground carbon stocks under differing silvicultural scenarios - Anne Ola; William Devos; Mathieu Bouchard; Marc J. Mazerolle; Patricia Raymond; Alison D. Munson (Forest Ecology and Management, 2024)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Cell Wall Composition and Underlying QTL in an F1 Pseudo-Testcross Population of Switchgrass - Desalegn D. Serba; Robert W. Sykes; Erica L. Gjersing; Stephen R. Decker; Guillaume Daverdin; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2016)

Quantitative Trait Loci (QTL) Underlying Biomass Yield and Plant Height in Switchgrass - Desalegn D. Serba; Guillaume Daverdin; Joseph H. Bouton; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2015)

Comparative Relationships and Chromosome Evolution in Switchgrass (Panicum virgatum) and Its Genomic Model, Foxtail Millet (Setaria italica) - Guillaume Daverdin; Bochra A. Bahri; Xiaomei Wu; Desalegn D. Serba; Christian Tobias; Malay C. Saha; Katrien M. Devos (BioEnergy Research, 2015)

Erratum to: Quantitative Trait Loci (QTL) Underlying Biomass Yield and Plant Height in Switchgrass - Desalegn D. Serba; Guillaume Daverdin; Joseph H. Bouton; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2014)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Slowly progressive spinocerebellar ataxia with extrapyramidal signs and mild cognitive impairment (SCA21) - J. Delplanque; D. Devos; I. Vuillaume; A. De Becdelievre; E. Vangelder; C. A. Maurage; K. Dujardin; A. Destée; B. Sablonnière (The Cerebellum, 2008)

Using an oilseed rape x wild /weedy relative gene flow index for the monitoring of transgenic oilseed rape - Yann Devos; A. De Schrijver; D. Reheul (Journal of Consumer Protection and Food Safety, 2007)

Comparative analyses reveal high levels of conserved colinearity between the finger millet and rice genomes - Srinivasachary; Mathews M. Dida; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2007)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

The genetic map of finger millet, Eleusine coracana - Mathews M. Dida; Srinivasachary; Sujatha Ramakrishnan; Jeffrey L. Bennetzen; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2006)

Allelic variation at the linked AP1 and PhyC loci in hexaploid wheat is associated but not perfectly correlated with vernalization response - J. Beales; D. A. Laurie; K. M. Devos (Theoretical and Applied Genetics, 2005)

An integrated genetic map and a new set of simple sequence repeat markers for pearl millet, Pennisetum glaucum - X. Qi; T. S. Pittaway; S. Lindup; H. Liu; E. Waterman; F. K. Padi; C. T. Hash; J. Zhu; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2004)

Patterns of chloroplast diversity among western European Dactylorhiza species (Orchidaceae) - N. Devos; D. Tyteca; O. Rasp; R. A. Wesselingh; A.-L. Jacquemart (Plant Systematics and Evolution, 2003)

Deciphering the action of aromatic effectors on the prokaryotic enhancer‐binding protein XylR: a structural model of its N‐terminal domain - D. Devos; J. Garmendia; V. de Lorenzo; A Valencia (Environmental Microbiology, 2002)
Summary The prokaryotic enhancer‐binding protein XylR is the central regulator of the toluene degradation pathway in Pseudomonas species. Copious genetic and biochemical data indicate that the N‐terminal domain of the protein (domain A) interacts directly with m‐ xylene, which renders the protein competent as a transcriptional activator. Single‐site and shuffling mutants of XylR or homologues have been reported to change or expand their effector profiles. Here, we follow a fold recognition approach to generate three‐dimensional models of the domain A of XylR and DmpR with the purpose of deciphering the molecular activity of this protein family. The model is based on the crystallographic data of the rat catechol O‐methyltransferase, a typical α / β fold, consisting of eight α ‐helices and seven β ‐strands. The fold identification is supported by physico‐chemical properties of conserved amino acids, distribution of residues characteristic of the sequence families and confrontation with experimental data. The model not only provides a rationale for understanding published experimental data, but also suggests the molecular mechanism of the activation step and is a potentially useful conceptual tool for designing regulators with predefined inducer specificities.

Comparative genetic analysis of the Aegilops longissima and Ae. sharonensis genomes with common wheat - H. Zhang; S. M. Reader; X. Liu; J. Z. Jia; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2001)

Construction of a BAC library of pearl millet, Pennisetum glaucum - S. Allouis; X. Qi; S. Lindup; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2001)

Genetic diversity within and among landraces of pearl millet (Pennisetum glaucum) under farmer management in West Africa - Carlos S. Busso; Katrien M. Devos; Gavin Ross; Michael Mortimore; William M. Adams; Michael J. Ambrose; Sharon Alldrick; Michael D. Gale (Genetic Resources and Crop Evolution, 2000)

Genetic control of domestication traits in pearl millet (Pennisetum glaucum L., Poaceae) - V. Poncet; F. Lamy; K. M. Devos; M. D. Gale; A. Sarr; T. Robert (Theoretical and Applied Genetics, 2000)

Comparative mapping reveals a complex relationship between the pearl millet genome and those of foxtail millet and rice - K. M. Devos; T. S. Pittaway; A. Reynolds; M. D. Gale (Theoretical and Applied Genetics, 2000)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Construction of RFLP-based maps of foxtail millet, Setaria italica (L.) P. Beauv. - Z. M. Wang; K. M. Devos; C. J. Liu; R. Q. Wang; M. D. Gale (Theoretical and Applied Genetics, 1998)

Relationships between the chromosomes of Aegilops umbellulata and wheat - H. Zhang; J. Jia; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 1998)

Comparative genetic maps of foxtail millet (Setaria italica) and rice (Oryza sativa) - K. M. Devos; Z. M. Wang; J. Beales; T. Sasaki; M. D. Gale (Theoretical and Applied Genetics, 1998)

Comparative genetics in the grasses - Katrien M. Devos; Michael D. Gale (Plant Molecular Biology, 1997)